Neoadjuvant tislelizumab combined with chemotherapy in locally advanced oral or oropharyngeal squamous cell carcinoma: a real−world retrospective study - Wu, Wen-Jie; Liu, Qian; An, Pu-Gen; Wang, Lin; Zhang, Jian-Yun; Chen, Yan; Zhang, Tong; Zhang, Jie (Frontiers in Immunology, 2023)
Objectives The treatment of locally advanced oral or oropharyngeal squamous cell carcinoma (LAOOPSCC) is surgery and radiotherapy or chemoradiotherapy but with unsatisfactory survival rate. Neoadjuvant programmed death-1 (PD-1) therapy are being used in several clinical trials. Therefore, in this retrospective study we aimed to determine the feasibility of neoadjuvant tislelizumab plus chemotherapy followed by surgery for LAOOPSCC. Materials and methods The clinical data of 33 patients with LAOOPSCC who received neoadjuvant PD-1 inhibitors and chemotherapy between April 2021 and October 2022 were retrospectively analyzed. Patients with stage III-IV LAOOPSCC received tislelizumab, albumin-bound paclitaxel, and cisplatin every 3 weeks (Q3W) for two cycles, followed by surgery and adjuvant radiotherapy or concurrent chemoradiotherapy. A median follow-up period was 20 months. Results The objective response rate (ORR) was 66.7%, with the major pathological response (MPR) rate at 54.5%, and the pathological complete response (pCR) rate was 33.3%. Sixteen patients underwent limited surgeries, and 15 patients were remitted from undergoing mandibulectomy and 9 patients were remitted from undergoing near total glossectomy or total glossectomy. A significant difference in the overall survival (OS) and disease-free survival (DFS) was observed in patients who achieved major pathological response (MPR) than who did not. The most common adverse events in neoadjuvant therapy were alopecia, decreased appetite or anorexia, leukopenia, and fatigue. Conclusion Neoadjuvant PD-1 inhibitors combined with chemotherapy are feasible and safe, with a high pathological response and possible organ preservation in oral or oropharyngeal squamous cell carcinoma. However, further studies with a larger cohort of patients and longer follow-up period is required to strengthen our findings and evaluate the survival benefits of the treatment.